TINJAUAN HUKUM ISLAM TERHADAP JUAL BELI ONLINE DENGAN SISTEM DROPSHIP (Studi Analisis Terhadap jual beli salam, wakalah dan samsarah) - Dewi, Tika (AT-TAFAHUM: Journal of Islamic Law, 2017)
Online business (selling- buying) has become prominent in the past few years ago as demand increases. This kind of business forms a positive effect of the development of internet which produces new business-men. Along with the development of online business, there emerges dropship system which is mostly undertaken by female entrepreneurs. Despite its negative effect, dropship system has positive influence, i.e. creating positive activities for women and therefore empowering them. The polemics of dropship is still going on. According to some Muslim jurists, dropship is forbidden (haram) because the practicioners of this system sell items only from picture. Moreover, the items sold have not been the property of the practicioners. This article deals with the benefit of salam, wakalah and samsarah contract used to accommodate the dropship system. The specification of contracts is explained in detail in order for this system to be undertaken as salam, wakalah and samsarah contract. The practicioners of dropship as muslam ilaih or wakil and supplier as muslam or muwakkil, or the practicioners of dropship as simsar with some conditions that should be accorded to the contract in the beginning of transaction.Keywords: Online business; dropship; salam, wakalah; samsarah.